An inductor-less universal switched-capacitor converter realizing dc/dc, ac/dc, dc/ac, and ac/ac conversion - Kei Eguchi; Ratanaubol Rubpongse; Akira Shibata; Yujiro Harada (Energy Reports, 2020)
For multi-applications, a novel universal switched-capacitor (SC) converter is proposed in this paper. The proposed converter consists of a rotation-type SC converter and a full-bridge circuit. Unlike the existing universal converter consisting of a series-parallel type converter and a full-bridge circuit, the rotation-type SC converter can offer an output voltage in all clock cycles by rotating the connection position of capacitors. Therefore, the proposed universal SC converter can achieve four types of conversion with high power efficiency, namely, step-up/step-down dc/dc conversion, step-down ac/dc conversion, step-up multilevel dc/ac conversion, and direct step-up/step-down ac/ac conversion. Through theoretical analysis, computer simulations, and bread board experiments, the characteristics of the proposed universal SC converter are evaluated. The result of these analyses demonstrates the feasibility of the proposed universal SC converter.
Keywords: 330; AC/AC converters; AC/DC converters; DC/AC converters; DC/DC converters; Inductor-less converters; Universal converters